Cosmic Cartography: tracing the large-scale structure around galaxy clusters - Cornwell, Daniel (2025)
On the largest cosmological distance scales, the cosmic web forms the backbone of the Universe. This network connects dark matter, galaxies and gas through a variety of structures. Galaxies that reside in different cosmic web environments are subject to a range of different physical mechanisms which can ultimately dictate the evolutionary path they take. At one end of the density scale, galaxy clusters exist that can quench and ultimately transform galaxies as they encounter the intracluster medium and the high density of galaxies. This results in a higher fraction of quiescent and early type galaxies in clusters compared to the field. Further down the density scale are cosmic filaments. A substantial fraction of the Universe’s mass budget is located in these environments. Filaments are a conduit through which galaxies are funneled through into the dense core of a galaxy cluster. Whilst there is strong evidence suggesting that galaxies experience environmental influence long before they reach the core of a cluster, (pre-processing), exactly where and when these changes take place is not well constrained.